Answer: x
=
4
,
y
=
6
Step-by-step explanation:
4
x
=
3
y
−
2 , 18
=
3
x
+
y
Solve for y
in the second equation.
Tap for more steps...
4
x
=
3
y
−
2
y
=
18
−
3
x
Replace all occurrences of
y in 4
x
=
3
y
−
2
with
18
−
3
x
.
4
x
=
3
(
18
−
3
x
)
−
2
y
=
18
−
3
x
Simplify
3
(
18
−
3
x
)
−
2
Tap for more steps...
4
x
=
−
9
x+
52
y
=
18
−
3
x
Move all terms in
4
x
=
−
9
x
+
52
to the left side and simplify.
Tap for more steps...
13
x
−
52
=
0
y
=
18
−
3
x
Solve for x
in the first equation.
Tap for more steps...
x
=
4
y
=
18
−
3
x
Replace all occurrences of
x in y
=
18
−
3
x
with 4
.
x
=
4
y
=
18
−
3
⋅
4
Simplify
18−
3
⋅
4
Tap for more steps...
x
=
4
y
=
6
The solution to the system of equations can be represented as a point.
(
4
,
6
)
The result can be shown in multiple forms.
Point Form:
(
4
,
6
)
Equation Form:
x
=
4
,
y
=
6